Full tensor properties of single‐domain tetragonal 0.63Pb(Mg1/3Nb2/3)O3–0.37PbTiO3 single crystal and their orientation dependence. Issue 10 (14th July 2016) - Jing, Yujia; Zheng, Limei; Lü, Weiming; Xi, Zengzhe; Zheng, Peng; Du, Juan; Zhang, Rui
Abstract : Single‐domain states have been achieved in [001]C ‐poled tetragonal 0.63Pb(Mg1/3 Nb2/3 )O3 –0.37PbTiO3 single crystal by a room‐temperature poling process. A comprehensive study of ferroelectric, piezoelectric, dielectric, and elastic properties of single‐domain crystal has been performed. High thickness shear piezoelectricity ( d 15 = 1410 pC/N) and transverse dielectric permittivity ( ϵ 11 T = 12250 ) is shown, and high anisotropy is exhibited according to the low longitudinal piezoelectric and dielectric parameters ( d 33 = 307 pC/N, ϵ 33 T = 775 ). The orientation dependence of longitudinal dielectric permittivity, piezoelectric constant, electromechanical coupling factor, and elastic compliance constants were calculated based on the single‐domain complete set. The maximum value of d 33 * was found 49° away from [001]C . Compared with domain‐engineered crystals, the single‐domain crystal possesses much higher shear piezoelectric and electromechanical properties, which show potential applications in shear‐wave transducers. This study provides important information of tetragonal Pb‐based relaxor single crystal, which is urgently needed for theoretical studies and device designs.